Assessment of motor coordination and dexterity of six years old children: A psychometric analysis - Olívia Souza Agostini; Lívia de Castro Magalhães; Alexandre Ferreira Campos (Universidade Estadual Paulista (UNESP), 2014)
Motor coordination of six-year-old children was examined using the Assessment of Motor Coordination and Dexterity, AMCD (Avaliação da Coordenação e Destreza Motora - ACOORDEM), in order to verify test-retest reliability and investigate whether motor performance is influenced by gender, type of school and residence location. Eighty-five children were evaluated, and their parents and teachers completed questionnaires. For test-retest reliability, the AMCD was repeated with 10 children. Mann-Whitney and chi-square tests identified significant influence of sex, type of school and residence location in just a few of the test items. The test-retest reliability was moderate in the items performance, and good to excellent in the majority of the questionnaires' items. We conclude that some items should be revised and normative tables for the identification of motor delay could be created considering only the age variable. Future studies should continue the process of validating the AMCD instrument with the assessment of younger children.